PHYSICAL ACTIVITY AND HEALTH: ANALYSIS OF HABITS OF PHYSICAL ACTIVITY AND BODY COMPOSITION IN PATIENT OF LOW SOCIOECONOMIC LEVEL WITH ETHYL DEPENDENCE OF THE CENTER OF SUPPORT PSYCHOSOCIAL ALCOHOL AND DRUGS (CAPES-AD) OF THE CITY OF JUAZEIRO OF THE NORTH, (Fiep Bulletin - online, 2014)
Introduction: Physical exercises act on different organic systems, it does not matter if it is on seemingly healthy people or on chemical dependents. Objective: To analyze the body composition, practice of physical activity and heart risk in alcoholics. Material and Methods: it comes from a descriptive, traversal study with 16 men of low socioeconomic level, average of 42,6+10,3 year-old age, alcoholic participants of the psychosocial support center (CAPS-AD), in Juazeiro do Norte city, Ceará, that underwent anamnesis questionnaires, perimeter verification, cutaneous folds, body mass (BM) and stature (ST), setting out of IBM, percentile of fat (% Fat) under Protocol of Guedes (1994), Weight of Stored Fat (WSF), Weight of Thin Mass (WTM) in kg and heart risk per waist circumference (WC) with point of cut of 90cm (men) and 80cm (women). The analytical Plan used SPSS 13.0 for descriptive analysis and inferential one. Level of trust of 5%. Results: We found: BM 60,26+10,62kg; ST 1,61+0,06m; IBM 23,17+3,96kg/m2; 50,0% normal and 37,5% overweight; % fat 16,29+6,87%; IWH 0,89+0,07, WSF 10,20 + 5,24kg, WTM 50,05+ 7,54kg, WC 82,24+10,60cm; 31,3% has been drinking for more than 30 years and 93,7% for more than 5 years; 56,3% are classified from active to very active; 25% play soccer, 25% walk and 6,3% use bicycle as a means of transportation; 43,8% insufficiently Active, 43,8 Active 12,5% Very Active; the "r" of Pearson found low correlations (r=0,115) between the time of drinking and heart risk; the correlations among WSF, IBM, WC,% fat and IWH were above 0,700; "t" of Student found significant differences between IBM and WC (p=0,000); WC and IWH (p=0,000); Conclusion: The body composition is in normal levels for physically active and insufficient active ones. No matter the activity level, ethyl dependence, time of ingestion and associated treatment to the physical activity, even irregularly, significant correlations associated to the heart risk were not observed.
Keywords: alcohol; body composition; physical activity